Application of time-lapse tTEM for groundwater monitoring and recharge in the San Luis Valley, Colorado, USA - Robinson, Julianne, author; Smith, Ryan G., advisor; Ronayne, Michael, committee member; Alves Meira Neto, Antonio, committee member (Colorado State University. Libraries, 2025)
The ability to measure groundwater availability, extraction, and recharge is becoming increasingly important as the climate changes and reliance on groundwater in water-stressed regions increases. Geophysical measurement methods like time-domain electromagnetic (TEM) surveys can address the need for cost-effective, high-resolution hydrostratigraphic data collection with greater spatial and temporal coverage than direct-sampling methods. Among other applications, these data can be used to map hydrostratigraphy and improve targeting of managed aquifer recharge. The application of TEM surveys for time-lapse studies could enable an expansion of the spatial and temporal scales of geophysical measurements, enhancing the capabilities in hydrologic applications such as delineating the infiltration front from groundwater recharge. Few studies have used mobile TEM surveys for time-lapse measurements. This study used geophysical datasets collected with towed time-domain electromagnetic (tTEM) surveys to track changes in subsurface resistivity at managed groundwater recharge sites in the San Luis Valley in south-central Colorado. Study sites were surveyed with tTEM approximately every six weeks over the course of the irrigation season to provide time-lapse datasets. Geostatistical tools were utilized to account for differences in measurement locations from survey to survey. Results show changes in subsurface resistivity consistent with recharge flows and observed soil water content throughout the irrigation season. Infiltration of recharge water at the study site followed lateral downward paths and was controlled primarily by the volume of recharge water applied. Minor variations were observed in lithology at depth, but the site had few geologic barriers to infiltration, making it a suitable location for managed recharge. This study demonstrates the capability of tTEM surveys to efficiently assess groundwater recharge over time through analysis of time-lapse measurements. This information can serve as an important addition to other forms of data to inform water management strategies, including managed aquifer recharge, in the San Luis Valley and other arid and semi-arid regions dependent on groundwater.
Keywords: managed aquifer recharge; time-domain electromagnetics; sustainable groundwater management; hydrogeophysics